DIRECTIONS FOR INCREASING ACTIVITY VOLUMES AS A VECTOR OF COMPETITIVE DEVELOPMENT OF RESTAURANT BUSINESS ENTERPRISES (Development Service Industry Management, 2024)
The article analyzes the issues of functioning and development of Ukrainian restaurant enterprises. It is shown that this is a type of economic activity that is most exposed to the negative impact of macroeconomic crises, shocks and upheavals. On the other hand, restaurant enterprises, as a rule, are small and have the lowest barriers to market entry. Accordingly, in the conditions of a full-scale war, restaurant operators experienced significant destabilization, including the destruction of enterprises and their infrastructure, restaurant facilities and warehouses, and the conditions for product transportation and logistics deteriorated. Thus, the task of implementing, on the one hand, an anti-crisis policy to restore their activities as a prerequisite for the development of entities of this type of economic activity, and, on the other hand, implementing a system of measures aimed at strengthening the competitive positions of entities in the restaurant business sector, was actualized. It is shown that one of the leading criteria and at the same time conditions for the competitive development of restaurant business enterprises is the volume of their income. The purpose of the article is to substantiate the directions of increasing the volume of activity in the system of management of the competitive development of restaurant business enterprises. The applied significance of the research results lies in the formation of management principles for making management decisions regarding the increase in the volume of economic activity of restaurant business entities. The scientific novelty of the research results lies in the further development of the methodology for increasing the volume of income of restaurant business entities.
Keywords: restaurant business enterprises; activity volumes; competitive development; anti-crisis tools; competitiveness; income; profit